Unlocking EFL Collaboration: Transformative Insights from Google Docs - Savina Nur Fitriani; Tatik Irawati (Jurnal Bahasa, Sastra, dan Studi Amerika, 2024)
This research aims to explore the practical application of Google Docs to facilitate collaborative writing within an EFL writing class at Universitas PGRI Jombang. Engaging 22 EFL students enrolled in an English paragraph writing course, the study employed participant observation and structured interviews as data collection methods. While all 22 students used Google Docs for collaborative writing during the participant observation phase, only a subset of 10 students were chosen for in-depth structured interviews to uncover their experiences. The findings revealed a positive reception among students toward Google Docs' functionalities, particularly real-time editing, commenting, and auto-saving. These tools significantly eased the exchange of ideas, fostering productive discussions and seamless real-time cooperation. However, the study also identified certain challenges, including uneven participation levels among students and potential distractions within the digital realm.